Plasma polymerization. IV. A systematic investigation of the inductively coupled RF plasma polymerization of pentafluorobenzene - Clark, D. T.; Abrahman, M. Z. (John Wiley & Sons, Inc., 1981)
The composition and gross structural features of plasma polymer films prepared by inductively coupled RF plasmas excited in pentafluorobenzene were investigated by ESCA as a function of the operating parameters. The rate of film deposition is dependent on the W/FM parameter and on site of deposition. The polymer formed in the glow region shows only small variations in structure as a function of power and pressure. Polymer films deposited in the regions away from the site of primary excitation typically have a higher fluorine content than those formed in the coil region; the stoichiometry for the latter is comparable to that of the starting material.